2020
DOI: 10.11591/ijere.v9i1.20501
|View full text |Cite
|
Sign up to set email alerts
|

Students’ views on database management systems course designed according to problem-based learning

Abstract: <span>The aim of this study was to design a learning environment supported by a problem-based learning method and to obtain students' views on this process. In this context, the Database Management Systems course was taught according to the problem-based learning method. The participants of the study consisted of 25 students from the 2nd-grade students studying in the Department of Computer Education and Instructional Technology in the spring semester of 2015 at Uludag University Faculty of Education. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 1 publication
1
1
0
Order By: Relevance
“…These authors found that the PBL approach is viewed positively by learners, who describe it as enjoyable, interactive, relevant, practical, and holistic. Uzun et al (2020) reached a similar conclusion. They concluded that the students were generally satisfied with the problem-based learning practices.…”
Section: Discussionsupporting
confidence: 61%
“…These authors found that the PBL approach is viewed positively by learners, who describe it as enjoyable, interactive, relevant, practical, and holistic. Uzun et al (2020) reached a similar conclusion. They concluded that the students were generally satisfied with the problem-based learning practices.…”
Section: Discussionsupporting
confidence: 61%
“…Problem-based learning can increase student activity in learning (Lapuz & Fulgencio, 2020). Problem-based learning provides opportunities for students to develop their social skills and responsibilities (Uzun et al, 2020). Problem-based learning helps students to solve problems and improve skills in working together (Nguyen, 2020).…”
Section: Pembahasanmentioning
confidence: 99%
“…Hal ini sesuai dengan pendapat Shofiyah dan Wulandari (2018) menyatakan bahwa pada langkah orientasi masalah guru menginformasikan tujuan-tujuan pembelajaran, memberi contoh masalah, mendeskripsikan kebutuhan-kebutuhan logistic penting, dan memotivasi siswa supaya terlibat aktif dalam kegiatan pemecahan masalah yang mereka pilih sendiri. Pembelajaran yang menghadirkan masalah memberikan kesempatan kepada siswa untuk mengembangkan keterampilan sosial dan tanggung jawabnya (Uzun et al, 2020); (2) pada langkah pengorganisasian belajar dengan multimedia guru membentuk siswa menjadi beberapa kelompok belajar, menyampaikan petunjuk melakukan diskusi, dan mengorganisasi tugas belajar sesuai masalah. Hal serupa dinyatakan oleh Shofiyah dan Wulandari (2018) bahwa pada langkah pengorganisasian belajar guru membantu siswa menentukan dan mengatur tugas-tugas belajar yang berhubungan dengan masalah tersebut; (3) pada langkah penyelidikan masalah guru mengawasi siswa ketika berdiskusi dan membimbing siswa dalam mencari sumber informasi untuk menyelesaikan masalah.…”
Section: Hasil Dan Pembahasanunclassified